Vibrio cholerae HlyA hemolysin is processed by proteolysis. - Hall, R H (1990)
The leukocidal activity of the Vibrio cholerae hemolysin (HlyA) was utilized to detect, enrich, and clone hybridoma cells expressing neutralizing monoclonal antibody in a new survivor selection protocol. A bank of 550 hybridoma clones was obtained from a mouse immunized with hemolysin by using standard techniques. The hybridoma bank was treated with a dose of HlyA hemolysin lethal to nonimmune clones. Five surviving hybridoma clones (X1 through X5) which possessed anti-HlyA activity were obtained. Western immunoblot analysis of V. cholerae culture supernatants with monoclonal antibody from clone X1 identified proteins with Mrs of 83,200, 71,600, and 60,300. Amino-terminal sequence analysis of the 71,600-Mr and 60,300-Mr forms showed homology with the published predicted sequence of HlyA. Our data indicate that proteolytic cleavage occurs between residues 120 and 121 (Glu-Leu) of the 83,200-Mr form, producing the 71,600-Mr form with the terminus NH2-L-L-F-T-P-F-D-Q-A-E-E-. Cleavage between residues 150 and 151 (Gly-Phe) releases the 60,300-Mr form with the terminus NH2-F-A-S-P-A-P-A-N-S-E-. Calculations based on the DNA sequence and the N termini indicated that the actual molecular masses of the 83,200-, 71,600-, and 60,300-Mr forms were, respectively, 79.4 kilodaltons (kDa), 68.6 kDa, and 65.3 kDa. Survivor selection and amino-terminal microsequencing offer powerful tools for the analysis of leukotoxic agents.